Mechanical Wave Concepts: Composing of Five-Step Conception Diagnostic Test, Validity and Reliability Test, and Student’s Profile Conception Level - Aretha Patricia Andriani; Frida Ulfah Ermawati (Berkala Ilmiah Pendidikan Fisika, 2022)
A mechanical wave is one of the Physics concepts related to everyday life. When the Authors interviewed some students at one of Gersik’s senior high schools, the Authors found that some students didn’t understand the concepts yet. Students thought that when a rope was moved up-down, the particles in the rope would be moved horizontally. The truth is that there was no movement of particles in the vibrated rope. Misconceptions must be detected immediately so as not to interfere with students' understanding of the following concepts. One way is by using a conception diagnostic test. The paper aims to report the composition of the five-step conception diagnostic test for Mechanical Wave concepts, its’ validity and reliability, and use it to identify students’ profile conception level in a Gresik’s senior high school. This study used ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model and data collection technique that used was developing of five-step question that passed through the validity and reliability stages. 13 questions were written and tested for their internal validity and 12 only questions declared valid 91.32%. The result of external validity in terms of a true fake (TF) and a wrong fake (WF) was 7.14% and 4.76% (valid as empirical content because of the TF and WF<10%). The conception diagnostic test was also valid as an empirical construct based on the Pearson Product Moment score because rab=0.575>rtable=0.4575 (significance level of 0.05), and 11 questions were finally declared valid and reliable. 40.40% of the 18 students for their profile conception level confirmed as Lack of Knowledge.